Current Standard of Care in Patients with Myelodysplastic Syndromes and Future Perspectives - Ioannis Chanias; Nicolas Bonadies (healthbook TIMES. Oncology Hematology)
The myelodysplastic syndromes (MDS) represent a heterogeneous group of clonal disorders caused by somatic driver mutations affecting the hematopoietic stem and progenitor cells (HSPCs). MDS are characterized by ineffective hematopoiesis with inflammation, dysplasia, cytopenia, and a variable risk of transformation into secondary acute myeloid leukemia (AML). As in many other malignancies, clonal evolution is caused by a stochastic accumulation of genetic hits in HSPCs with a selective pressure imposed by intrinsic growth advantage, extrinsic factors, and loss of immunogenic tumor surveillance. With the aging of the population, higher diagnostic sensitivity in detecting clonality, and improved cancer survivorship, incident cases are on the rise with a relevant impact on health care resources. WHO classification, disease-based as well as patient-based risk-stratifications remain the cornerstone for appropriate treatment allocation. The advent of next-generation sequencing (NGS) has improved our understanding of the genetic origin of the disease. This is paving the way to improve diagnostic accuracy for detection of clonality, risk stratification, prognostication, treatment allocation as well as monitoring of response to therapy. In lower-risk MDS patients, median survival reaches 3 to 8 years, and mortality is mainly caused by cytopenia-related complications (cardiovascular events, infections, and bleeding). Therefore, the treatment for these patients should focus on the improvement of cytopenia, inflammation, quality of life as well as disease progression. In contrast, in higher-risk MDS patients, median survival ranges from 1 to 3 years, and death from transformation to AML exceeds non-leukemic mortality. Treatment in these patients is aimed to delay progression to AML and improve overall survival. The only curative treatment option remains allogeneic hematopoietic stem cell transplantation, which is an intensive treatment requiring careful selection of patients. Most patients are not eligible due to advanced age or comorbidities and they receive palliative treatment with transfusions, growth factors, and hypomethylating agents. New treatment options are on the horizon that promise to improve cytopenia, reduce progression to higher-risk MDS/AML, and prolong survival. However, the Holy Grail that rejuvenates HSPCs with the abrogation of clonal evolution remains out of our reach.